2002
DOI: 10.1097/00002030-200211220-00006
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproduction in HIV-1-serodifferent couples

Abstract: Selected spermatozoa may be positive for HIV RNA detection even in treated patients. Viral validation of processed semen is necessary in ART programmes for serodifferent couples, particularly in men with only partially or poorly controlled HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Importantly, our data indicate that early TGCs remained viable in culture after viral entry, integration, and protein expression, suggesting that viral integration was not detrimental to these cells. Clonal infection of the male germ line up to spermatozoa is suggested by reports of HIV DNA in a low percentage of ejaculated sperm (16)(17)(18)(19)(20)(21)23). Indeed, spermatozoa do not support HIV entry, are transcriptionally silent, and have a highly compact chromatin, thus preventing HIV replication steps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, our data indicate that early TGCs remained viable in culture after viral entry, integration, and protein expression, suggesting that viral integration was not detrimental to these cells. Clonal infection of the male germ line up to spermatozoa is suggested by reports of HIV DNA in a low percentage of ejaculated sperm (16)(17)(18)(19)(20)(21)23). Indeed, spermatozoa do not support HIV entry, are transcriptionally silent, and have a highly compact chromatin, thus preventing HIV replication steps.…”
Section: Discussionmentioning
confidence: 99%
“…We and others found that HIV/SIV strains in semen are locally produced in a subset of individuals (reviewed in reference 13) and arise from several organs within the male genital tract (14). Interestingly, HIV-1 can associate with spermatozoa in vitro (15) and was detected by some authors in a small proportion of patients' sperm (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Since spermatozoa have a highly compact nucleus and are transcriptionally silent, this detection may suggest infection of their germ cell progenitors in the testis.…”
mentioning
confidence: 99%
“…Sperm parameters that reflect fertility are significantly impaired in HIV-1 infected men. Measurements including semen volume, sperm motility, concentration and morphology are adversely affected (8890). Semen parameters correlate positively with CD4 counts (91), which suggests that patients with full blown AIDS are less fertile than healthier HIV-1 infected males.…”
Section: Male Infertility and Hiv/aidsmentioning
confidence: 99%